(untitled) (Bangladesh Journal of Medical Science, 2023)
Background: Oxidation of hepatocyte mitochondria due to iron overload led to hepatocyte injury, elevated Transforming growth factor- β (TGF- β), and fibrosis. Fibrosis starts with stellate cell fibrogenesis activated by chronic hepatocyte injury. Liver fibrosis is the main cause of morbidity and mortality in iron overload. Deferasirox is an iron chelation drug serving to bind iron overload and have an antifibrotic effect. Aim: To examine the effect of deferasirox on liver fibrosis prevention due to iron overload. Methods: This experimental research used a post-test only control group design on male Balb/c mice that were randomly divided into 3 groups, each n=5. Group 1 (NaCl+S) was administered with 0.3 cc Na Cl 0.9% through intra peritoneal (I.P) injection and drug solvent (Aquabidest, CMC and Nipagin) per oral (P.O) intermittently. Group 2 (Fe+S) was administered with 0.3 cc 1.5 mg Fe+sucrose (Venofer®) through I.P injection and drug solvent (Aquabidest, CMC and Nipagin) P.O intermittently. Group 3 (Fe+Dfx) 0.3 cc 1.5 mg Fe+sucrose (Venofer®) I.P injection, and deferasirox 20 mg/kgBW/day P.O intermittently. All of the treatments were given for 60 days. The fibrosis area fraction of the liverwas assessed using software ImageJ. Results: The average fibrosis area fraction of group 1 was 0.00 ± 0.00%, group 2 was 9.17 ± 8.54% and group 3 was 1.38 ± 0.20%. The fibrosis area fractions between groups 2 and 3 were significantly different with p value 0.000 (p<0.05). The body weight of group 2 was higher than that of groups 3 and 1. Conclusions: Iron overload causes liver fibrosis in male Balb/c mice. Deferasirox administration may lower the area of liver fibrosis in male Balb/c mice due to iron overload. Bangladesh Journal of Medical Science Vol. 22 No. 01 January’23 Page : 84-90